Attosecond hole migration in benzene molecules surviving nuclear motion - Despré, Victor; Marciniak, A.; Loriot, V.; Galbraith, M. C. E.; Rouzée, A.; Vrakking, M. J. J.; Lépine, F.; Kuleff, Alexander I. (The journal of physical chemistry letters, 2015)
Hole migration is a fascinating process driven by electron correlation, in which purely electronic dynamics occur on a very short time scale in complex ionized molecules, prior to the onset of nuclear motion. However, it is expected that due to coupling to the nuclear dynamics, these oscillations will be rapidly damped and smeared out, which makes experimental observation of the hole migration process rather difficult. In this Letter, we demonstrate that the instantaneous ionization of benzene molecules initiates an ultrafast hole migration characterized by a periodic breathing of the hole density between the carbon ring and surrounding hydrogen atoms on a subfemtosecond time scale. We show that these oscillations survive the dephasing introduced by the nuclear motion for a long enough time to allow their observation. We argue that this offers an ideal benchmark for studying the influence of hole migration on molecular reactivity.